Evaluation of Systems Contractor's Ability to Deliver a Solution to Offer During an Engineer‐To‐Order Bidding Process. Issue 4 (10th January 2020) - Sylla, Abdourahim; Vareilles, Elise; Coudert, Thierry; Aldanondo, Michel; Geneste, Laurent
ABSTRACT: To increase their business volume and remain competitive, systems contractors must propose competitive and feasible solutions to customers. However, Engineer‐To‐Order industrial situations become challenged by the lack of relevant information. This article, to help companies to overcome this problem, presents two confidence indicators, their evaluation methods, and a way to use them during a design process. These indicators allow evaluating a company's future ability to offer a solution during a bidding process.